2015
DOI: 10.1097/cmr.0000000000000138
|View full text |Cite
|
Sign up to set email alerts
|

MelanA-negative spindle-cell associated melanoma, a distinct inflammatory phenotype correlated with dense infiltration of CD163 macrophages and loss of E-cadherin

Abstract: MelanA is a known melanocyte marker and is important in melanoma diagnostics. Some tumours, however, show loss of MelanA expression and may therefore be difficult to distinguish from tumours of mesenchymal origin. Pure spindle-cell melanoma is a rare event, and little is known about its biological background and prognosis. However, morphological changes towards a more mesenchymal shape and cellular dedifferentiation may correlate with reactivation of important developmental programmes (epithelial-to-mesenchyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
10
1
1
Order By: Relevance
“…Spindle cell morphology in melanomas is thought to represent a more immature, dedifferentiated, mesenchymal phenotype. 34,35 PD-L1 expression has previously been associated with an epithelial to mesenchymal transition (EMT) in other tumor types, 36,37 though the relationship between PD-L1, EMT, and the presence of a cytotoxic T-cell infiltrate was not assessed. Our findings comparing the pure desmoplastic type vs other CSD melanomas raise the possibility that it could be a combination of EMT (as exemplified here by a spindle cell morphology) and a diffusely-arrayed antitumor immune response that may contribute to increased levels of PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Spindle cell morphology in melanomas is thought to represent a more immature, dedifferentiated, mesenchymal phenotype. 34,35 PD-L1 expression has previously been associated with an epithelial to mesenchymal transition (EMT) in other tumor types, 36,37 though the relationship between PD-L1, EMT, and the presence of a cytotoxic T-cell infiltrate was not assessed. Our findings comparing the pure desmoplastic type vs other CSD melanomas raise the possibility that it could be a combination of EMT (as exemplified here by a spindle cell morphology) and a diffusely-arrayed antitumor immune response that may contribute to increased levels of PD-L1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental mouse studies have shown that mast cells promote B16 melanoma growth and/or metastatic spread through mast cel-derived HIF-1a (45). Histomorphologic analyses of nine primary melanomas with a distinct MelanA-negative clone next to a MelanApositive clone discovered a significant correlation of the loss of MelanA expression with an increased infiltration of CD163 þ macrophages and a spindle-shaped tumor cell morphology in comparison with MelanA expression tumor areas (46). These observations as well as our results suggest that reciprocal tumor-immune cell interactions shape the microenvironment and the melanoma cell phenotype in mouse and man.…”
Section: V600e -Nf1mentioning
confidence: 99%
“…This inflammatory phenotype of macrophages is associated with loss of MelanA expression, possible marker of a more invasive tumor cells 27 . Classic inflammation players, like complement system elements, were also studied in relation to tumorigenesis.…”
Section: Cells That Sustain the Inflammatory Milieumentioning
confidence: 99%